Quality of life, immunomodulation and safety of adjuvant mistletoe treatment in patients with gastric carcinoma - a randomized, controlled pilot study - Kim Kab-Choong; Yook Jeong-Hwan; Eisenbraun Jürgen; Kim Byung-Sik; Huber Roman (BMC, 2012)
Abstract Background Mistletoe (Viscum album L.) extracts are widely used in complementary cancer therapy. Aim of this study was to evaluate safety and efficacy of a standardized mistletoe extract (abnobaVISCUM® Quercus, aVQ) in patients with gastric cancer. Patients and Methods 32 operated gastric cancer patients (stage Ib or II) who were waiting for oral chemotherapy with the 5-FU prodrug doxifluridine were randomized 1:1 to receive additional therapy with aVQ or no additional therapy. aVQ was injected subcutaneously three times per week from postoperative day 7 to week 24 in increasing doses. EORTC QLQ-C30 and -STO22 Quality of Life questionnaire, differential blood count, liver function tests, various cytokine levels (tumor necrosis factor (TNF)-alpha, interleukin (IL)-2), CD 16+/CD56+ and CD 19+ lymphocytes were analyzed at baseline and 8, 16 and 24 weeks later. Results Global health status (p <0.01), leukocyte- and eosinophil counts (p ≤0.01) increased significantly in the treatment group compared to the control group. Diarrhea was less frequently reported (7% vs. 50%, p=0.014) in the intervention group. There was no significant treatment effect on levels of TNF-alpha, IL-2, CD16+/CD56+ and CD 19+ lymphocytes and liver function tests measured by ANOVA. Conclusion Additional treatment with aVQ is safe and was associated with improved QoL of gastric cancer patients. ClinicalTrials.Gov Registration number NCT01401075.